ANALISIS EFISIENSI PASAR MODAL KONVENSIONAL BENTUK LEMAH DI BURSA EFEK INDONESIA PERIODE 2014-2015 - Ade Lisa Istifarida; Salamatun Asakdiyah (Universitas Ahmad Dahlan, 2017)
The purpose of this study is to determine efficiency in a weak form conventional capital market in Indonesia using stock price data weekly in the 2014-2015 period. Techniques in testing market efficiency forms. This weakness uses a purposive sampling technique as well as a method for data collection using the documentation method. Obtained 36 companies which is included in the LQ-45 index which is used as a research sample. Testing the hypothesis of a weak form of capital market efficiency using the run test test. The results of this study, that the conventional capital market is efficient in a weak form using stock price information for the period research. It is proven by 33 shares (91.7%) moving randomly (random) and 3 shares (8.3%) move non-randomly (not randomly). Then it can be concluded that the conventional capital market is efficient in its form weak.